2012
DOI: 10.1371/journal.pone.0030420
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive and Tactile Factors Affecting Human Haptic Performance in Later Life

Abstract: BackgroundVision and haptics are the key modalities by which humans perceive objects and interact with their environment in a target-oriented manner. Both modalities share higher-order neural resources and the mechanisms required for object exploration. Compared to vision, the understanding of haptic information processing is still rudimentary. Although it is known that haptic performance, similar to many other skills, decreases in old age, the underlying mechanisms are not clear. It is yet to be determined to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
47
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(53 citation statements)
references
References 96 publications
5
47
1
Order By: Relevance
“…We found that older adults (those older than age 70) were less accurate than young adults in foot touch detection, kinesthesia, and haptic recognition; we did not find consistent changes for older adults on wrist position sense and texture discrimination. Although others have reported that women's decline in accuracy and speed for exploration of unfamiliar objects is greater than men's (Kalisch et al, 2012), we found a gender difference only for brief kinesthesia, and women were more accurate. Some researchers have demonstrated both neural changes in proprioception specifically (Goble et al, 2012;Goble, Lewis, Hurvitz, & Brown, 2005) and plasticity of the somatosensory cortex more globally in older adults, findings that may represent a compensatory mechanism to counterbalance cortical degeneration (Pellicciari, Miniussi, Rossini, & De Gennaro, 2009).…”
Section: Patterns Of Somatosensory Perception Across the Lifespancontrasting
confidence: 97%
See 1 more Smart Citation
“…We found that older adults (those older than age 70) were less accurate than young adults in foot touch detection, kinesthesia, and haptic recognition; we did not find consistent changes for older adults on wrist position sense and texture discrimination. Although others have reported that women's decline in accuracy and speed for exploration of unfamiliar objects is greater than men's (Kalisch et al, 2012), we found a gender difference only for brief kinesthesia, and women were more accurate. Some researchers have demonstrated both neural changes in proprioception specifically (Goble et al, 2012;Goble, Lewis, Hurvitz, & Brown, 2005) and plasticity of the somatosensory cortex more globally in older adults, findings that may represent a compensatory mechanism to counterbalance cortical degeneration (Pellicciari, Miniussi, Rossini, & De Gennaro, 2009).…”
Section: Patterns Of Somatosensory Perception Across the Lifespancontrasting
confidence: 97%
“…Young adults are better at recognizing raised letters and textures than older adults (Manning & Tremblay, 2006). Others have reported that two-point discrimination and haptic discrimination diminish in adults age 65 yr and older (Kalisch, Kattenstroth, Kowalewski, Tegenthoff, & Dinse, 2012;Lederman & Klatzky, 2009;Schumm et al, 2009;Stevens et al, 2003) and were significantly less accurate for people who tend to fall (Melzer, Benjuya, & Kaplanski, 2004). Diminishing proprioception and sensitivity across adulthood have also been documented (Laszlo & Bairstow, 1980;Ribeiro & Oliveira, 2007;Stevens et al, 2003;Wickremaratchi & Llewelyn, 2006).…”
mentioning
confidence: 98%
“…If the discrimination distance between 2 points is less than the measured minimum distance, then we wrongly perceive only 1 point despite being stimulated by the 2-point indenter. Moreover, the test showed that the minimum 2-point discrimination distance of elderly people is larger than that of young people (Stevens and Choo, 1996;Kalisch et al, 2012;Pleger et al, 2016). The discrimination distance of young people is approximately 2.0 mm, and that of elderly people is approximately 3.5 mm.…”
Section: Contact With a 2-point Indentermentioning
confidence: 91%
“…This could reflect the better treatment of spatial information by the right hemisphere. Moreover, studies have often reported that men are either more strongly lateralized or more accurate than women (e.g., Dawson, 1981;Kalisch, Kattenstroth, Kowalewski, Tegenthoff, & Dinse, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The results are expected to become reference data in the clinical study of TOR disorders. Finally, since a variety of studies reported stronger laterality effects in men with respect to women in the tactile modality (e.g., Dawson, 1981;Kalisch et al, 2012;Lenhart & Schwartz, 1983), possible sex diffrence also explored additionally.…”
Section: Introductionmentioning
confidence: 99%